Building Synonym Set for Indonesian WordNet using Commutative Method and Hierarchical Clustering - Valentino Rossi Fierdaus; Moch Arif Bijaksana; Widi Astuti (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
WordNet is a compilation of Synonyms Set (synset), which consists of the words that have the same synonymous. The development of Indonesian WordNet has a goal to build an application that can accommodate and exhibit the relation of words. Synonym Set is a set composed of one or more words that have a similar meaning or synonym relation originated from the Indonesian Thesaurus. In previous studies, the establishment of synsets were transmitted with several approaches, one of which was the cluster ring to produce synsets and WSD (Word Sense Disambiguation). In this research, research is held up to discover the semantic similarities between words in the Indonesian Thesaurus automatically, and also to know the performance of the Agglomerative Hierarchical Clustering method for the development of Indonesian synsets. To calculate performance and evaluation, this research is using the F-measure method involving the gold standard